Analysis of the Understanding and Political Awareness of New Voters in the 2024 Election: A Siyasah Dusturiyah Perspective - Azhar, Nabila; Sutiana, Yana; Tresnayadi, Budi (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2024)
Due to their significant influence, new voters have a dynamic political orientation and are crucial targets in elections. In the 2024 General Election, Generation Z and millennials will dominate the voter demographic, comprising 56.45% of 204 million voters, thus holding substantial potential in determining election outcomes. This study examines new voters' political awareness and participation in the Cibeunying Kidul Sub-district, focusing on the influence of political understanding, environmental support, family socialization, and political education. This research employs a juridical-empirical approach using interviews and participatory observation to gather data from new voters aged 17-21. Findings indicate that new voters' political awareness is heavily influenced by family habits and guidance, highlighting the need for more intensive political education. Some new voters exhibit apathy due to distrust in the political system. Therefore, the role of the KPU (General Election Commission) in socializing elections to new voters is crucial to enhance their participation. From the siyasah dusturiyah perspective, political participation is part of obedience to the leader and a mandate that must be fulfilled. Elections in Islam resemble deliberations to select a leader who will be sworn in. New voters' participation in elections aligns with the amar ma'ruf nahi munkar principle. Enhanced political awareness among new voters will increase their participation in elections, thereby strengthening the quality of democracy in Indonesia.